Application of Kahoot Online Media to Critical Thinking in Mathematics for Grade V Students of SDN 1 Tambahrejo - Arneta Putri Dwi Amanda; Eka Zuliana; Lovika Ardana Riswari (RANGE: Jurnal Pendidikan Matematika, 2024)
The aim of this research is to determine the influence of the online media Kahoot on the average results of critical thinking scores in mathematics for class V students. Mathematics is the main subject introduced at the elementary, middle and high school levels. This is different from conditions in the field where mathematics is a fear for students because they think that this subject is difficult. This is proven by the low average scores obtained by students. Students sometimes don't focus on working on questions and get bored quickly because they deliver material that seems monotonous. This assistance in mathematics subjects, especially critical thinking skills, was experienced by fifth grade students at SDN 1 Tambahrejo. The type of research is quantitative Pre Experimental in a One Group Pretest Posttest design. Data collection uses several techniques, namely observation, interviews, documentation and tests. In this research, the sample used was 19 fifth grade students at SD N 1 Addahrejo. The results of this research show that the average value of the pretest data is 41.37, while the average posttest value shows a result of 80.58. Based on this data, students experienced an increase in the average value of 39.21. Based on the presentation of the results of the data obtained, it shows that there is an influence, namely the difference in the average value of critical thinking in mathematics for class V students through the use of the online media Kahoot. Keywords: critical thinking, elementary school, kahoot, media